PENGARUH KEPERCAYAAN PADA ATASAN, KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN - Untung Widodo (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2009)
The development and fluency of a company will very depend on its workers’ jobproductivity. Basicly, productivity has a meaning as a comparison between output and input. In 2003 – 2007, the level of job productivity especially salesmen at PT Nyonya Meneer Semarang on sale target reachment which is settled by the company hasn’t done well. Although sale is also influenced by external factors, but internal factors is predicted influences the success ofsale target reachment. Therefore the problem in this research is what factors which influence the salesmen productivity level which effects the sale target in 2007 doesn’t reach are. The purpose of this study are : (1) to test the credibility influence to the leader on workers’ productivity, (2) to test the organization commitment influence on workers’ productivity, (3) to test the job satisfaction on workers’ productivity, (4) to test the credibility influence to leader, organization’s commitment and job satisfaction symultantly on workers’ productivity.This research uses primer data and seconder data, the questioner result which is spreaded out to responden counts 111 salesmen of PT Nyonya Meneer Semarang and also uses seconder data which is gotten from company’s report and literature related to the research hyphothesa is regretion analysis.The analysis result can be known that the first hyphothesis can be concluded that credibility to the leader has a significant positive influence on workers’ productivity. The second hyphothesis can be concluded that organization’s commitment has a significant positive influence on workers’ productivity. The third hiphothesis can be concluded that credibility to the leader and organization’s commitment have a significant positive influenceon workers’ productivity. The fourth hyphothesis can be concluded that there is a significant positive influence among variables : credibility to the leader, organization’s commitment and job satisfaction togetherly on job productivity.